Can rotational thromboelastometry predict thrombotic complications in reconstructive microsurgery?. Issue 4 (21st October 2013) - Kolbenschlag, Jonas; Daigeler, Adrien; Lauer, Sarah; Wittenberg, Gerhard; Fischer, Sebastian; Kapalschinski, Nicolai; Lehnhardt, Marcus; Goertz, Ole
<x xml:space="preserve">Abstract</x> Thrombotic occlusion of the microvascular pedicle is the major reason for flap loss. Thus, identifying patients who are at risk for such events is paramount. Rotational thromboelastometry (RTE) is widely used to detect coagulopathy and hypercoagulable states. The aim of our study was to assess its diagnostic value in reconstructive microsurgery. In all 181 patients undergoing free tissue transfer at our department between February 2010 and November 2011 preoperative RTE was performed. In addition, coagulation values as well as patient's demographic data, cause and localization of defect, type of flap and surgical revisions were recorded. The majority of patients was male (59.6%) with traumatic (59.7%) defects located on the lower extremity (60.3%). ALT was the most often used flap (35.9%). Preoperatively, 36.5% of patients had a hypercoagulable RTE (higher than physiological RTE values; intrinsic (ICPT) or extrinsic (ECPT) mean clot firmness (MCF) >72mm or functional fibrinogen (ICF) MCF >25mm). A total of 28 primary thrombosis of the microvascular pedicle occurred, 11 of those in‐patients with a hypercoagulable state. Total flap loss rate because ofthrombosis was 7.7% (n = 14). Both a hypercoagulable RTE assay and a functional fibrinogen to platelet ratio (FPR) of >43 (MCF value of ICF divided by the MCF value of ICPT) were significant predictors of thrombotic flap loss when performing multivariate binary logistic regression, co‐factoring for age, sex, and comorbidities (p = 0.036 and 0.003, respectively). RTE seems to be able to identify patients that are prone to thrombotic complications and might be used as a screening tool. © 2013 Wiley Periodicals, Inc. Microsurgery 34:253–260, 2014.